Divorce and its role in the problems of fostered children: Department of Social Services in Sharjah as a model - Alzarouni, Mariam; Altaii, Alaa (Al-Adab Journal, 2023)
Family stability is a relative situation, which may not always be available due to many factors. The family may be exposed to crises of a social and psychological nature that lead to the cracking and imbalance of family relations, such as divorce, which affects the family in general and children in particular, so the study aimed to identify the problems of children The children (behavioral, educational, psychological, social) and the significance of the differences according to gender (males - females), and the age at the time of divorce. Constructivism as its theoretical framework. The sample size of the study was (60) male and female students, they were chosen by simple random method. Among the most important findings of the study, that children suffer from many problems (behavioral, psychological, academic and social) with a degree ranging from large to medium, and there are statistically significant differences for demographic variables, gender and age, and the study recommended the responsible ministries to activate the role of family centers to enhance stability among Cuddled children.